Toxicity and Genotoxicity of Pendimethalin in Maize and Onion - Nuttapol Promkaew; Puangpaka Soontornchainaksaeng; Sansern Jampatong; Piangchan Rojanavipart (Agriculture and Natural Resources, 2010)
Herbicides are applied widely to maize crops. Frequently, these chemicals cause genetic change. Thus, this study was carried out with the aim to modify the Allium test using maize and onion to evaluate the toxicity and genotoxicity of pendimethalin. The effective concentration (EC), mitotic index (MI) and chromosomal aberrations found in treated root meristems of onion (Allium cepa) and three cultivars of Zea mays (HSSS, Insee2 and Suwan4452) were used as the endpoints of toxic and genotoxic evaluation. The results revealed that pendimethalin affected the toxicity and genotoxicity on three cultivars of maize and on onion. The percentages of recommended dose (7.5 ml/L) of pendimethalin at EC30, EC50, and EC70 were 0.05, 0.08 and 0.15% for HSSS, 0.02, 0.04 and 0.08% for Insee2, 0.02, 0.05 and 0.09% for Suwan4452, and 0.07, 0.16 and 0.29% for onion, respectively. Pendimethalin caused a significant increase in both the mitotic index and the frequency of chromosomal aberrations for all plants in the study. The types of chromosomal aberrations detected in root cells were fragments, bridges, laggards, multipolar and micronuclei. Moreover, abnormal metaphase (C-mitosis) and polyploidy, as well as the accumulation of metaphase cells, were also found in treated root cells. The results of this study will provide additional data on the toxicity and genotoxicity of the herbicide and also assist in environmental pollution monitoring.